Coronary computed tomography angiography as a screening tool for moderate-high risk asymptomatic type 2 diabetes mellitus patients - Liu, Qiaolu; Qiu, Jianfeng; Sun, Shuxin; Wang, Xiaoqiang; Sun, Zhanguo; Zhao, Huihui (Frontiers in Cardiovascular Medicine, 2022)
Background: There are few data on the clinical significance of coronary computed tomography angiography (CCTA) in asymptomatic type 2 diabetes mellitus (T2DM) patients. We performed a retrospective study to evaluate coronary heart disease screening in asymptomatic patients with T2DM using CCTA and coronary heart disease risk stratification prediction. Methods: Data from 141 type 2 diabetes mellitus patients (58±8 years, 57% males) without known symptoms suggestive of coronary heart disease who underwent CCTA were retrospectively analyzed. The patients were classified into three subgroups based on United Kingdom prospective diabetes study (UKPDS) coronary heart disease risk stratification prediction. Ninety-three patients without diabetes mellitus and coronary heart disease who underwent CCTA successively were chosen as the control group. The segment involvement score (SIS), segment stenosis score (SSS), stenosis coefficient (SC) and severe proximal plaque (SPP) positive ratio based on CCTA data were evaluated and compared among the groups. Results: Compared with the patients in the control group, patients in the moderate-high risk DM groups had higher scores on the SIS, SSS and SC and a higher SPP positive ratio (all p values <0.001), and no difference was observed between the low-risk group and the control group (p=0.147, p=0.116, p=0.132, p=0.663, respectively). Compared with patients in the control group, the patients in the moderate-high risk DM groups had increased odds of SIS>3 (OR=7.838, p<0.001; OR=5.325, p<0.001, respectively), SSS>5 (OR=6.750, p<0.001; OR=6.027, p<0.001, respectively) and obstructive stenosis (OR=7.900, p<0.001; OR=6.320, p<0.001, respectively). Conclusions: The moderate-high coronary heart disease risk patients had increased odds of obstructive coronary artery stenosis, and the distribution of coronary artery stenosis was more extensive and more severe in that group compared to the patients without diabetes mellitus and coronary heart disease. Coronary heart disease can be effectively screened in moderate-high risk asymptomatic type 2 diabetes mellitus patients using CCTA.